2017
DOI: 10.1016/j.sjbs.2017.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of curcumin on glucose and lipid metabolism, FFAs and TNF-α in serum of type 2 diabetes mellitus rat models

Abstract: Treatment with curcumin can significantly improve the metabolic disorder of glucose and lipid, enhance the sensitivity to the insulin, and ameliorate the resistance to insulin of the type II DM rats. Meanwhile, this treatment method can also significantly decrease the level of FFA and TNF-α in serum of type II DM rats. Thus, we inferred that the mechanism of curcumin to improve the insulin resistance might be correlated with the decreases of FFA and TNF-α in serum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 15 publications
2
33
1
Order By: Relevance
“…According to the 2016 Global Report on Diabetes of the World Health Organization (WHO), 422 million people (or 8.5% of the population) were suffering from DM globally. DM and its complications affect the quality of life of human beings, and have become a significant global public health problem [3]. Because of the continuous increase in the numbers of patients and aggravation in prevalence, DM is one of the major chronic noninfectious diseases worldwide, and has imposed a heavy burden on human beings [3].…”
Section: Introductionmentioning
confidence: 99%
“…According to the 2016 Global Report on Diabetes of the World Health Organization (WHO), 422 million people (or 8.5% of the population) were suffering from DM globally. DM and its complications affect the quality of life of human beings, and have become a significant global public health problem [3]. Because of the continuous increase in the numbers of patients and aggravation in prevalence, DM is one of the major chronic noninfectious diseases worldwide, and has imposed a heavy burden on human beings [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, treatment with C. longa, V. album and pre-eminently co-treatment with C. longa + V. album showed a potent ability in increasing the antioxidant levels and scavenging free radicals which perhaps aggravated diabetic conditions. Plant source bioflavonoids have been reported to be an excellent candidate for free radical scavenging [58] therefore, curcumin from C. longa and lectin from V. album are excellent antioxidant and has also been demonstrated to be potent in the management of diabetes [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…We tested the effect of curcumin analogs in a STZinduced model of type 1 diabetes. Previous studies have shown that curcumin reduces glycemia in type 2 models (36), and improves insulin resistance (37). Therefore, in type 2 diabetes, curcumin may provide protective effects by reducing the stimulus (hyperglycemia and dyslipidemia) (38).…”
Section: Toxicity Studies and The Effects Of Curcumin Analogs On Bloomentioning
confidence: 99%